Homestay Development as a Community-Based Business in Dolok Martumbur Tourism Village, Muara District, Utara Tapanuli Regency - Julianto (Politeknik Pariwisata Medan, 2021)
This research is a research on Homestay Development as a Community-Based Business in Dolok Martumbur Tourism Village, Muara District, North Tapanuli Regency. This study aims to determine the management, standards of homestay and the role of the government towards Homstey as a community-based business in the Tourism Village of Dolok Martumbur, Muara District, North Tapanuli Regency. Data was collected by observation, interviews, questionnaires, and literature study. The researcher uses a qualitative descriptive research method because this study explores the phenomenon of Homestay Development as a Community-Based Business in the Tourism Village of Dolok Martumbur, Muara District, North Tapanuli Regency. Meanwhile, there are 25 homestays that are managed by local people because they use some of their houses as a place to stay. The homestay management system is managed by the local community. The community plays a role in two important aspects of tourism in the tourist village of Dolok Martumbur, Muara District, Homestay in improving service quality and taking part in various tourism activities. From the management related to the development of homestays, three important aspects are taken, namely cleanliness, comfort and security which still do not meet the standards where the government has provided assistance in the construction of homestays, but it is not in accordance with the standardization of homestays